Treating a single, stiff, second-order ODE directly - Suleiman, M.B.; Gear, C.W. (Elsevier, 1989)
The stability of direct methods for second-order systems is examined. The methods, suggested by Krogh, are generalized BDF methods. The control of stepsize to ensure stability is examined and criteria for deciding when to switch between methods are discussed.